Salmonella serotypes isolated from local cheese in Mosul city - H H Ali (Iraqi Journal of Veterinary Sciences, 2005)
Total of 60 random samples of local fresh, non-salted cheese collected from different markets of Mosul city were found to be contaminated with Salmonella 7 (11.7%). Three different Salmonella serotypes were identified with S. agona was the most prevalent serotype accounting for 3 (42.86%) of all isolates followed by S. typhimurium 2 (28.57%) and S. anatum 2 (28.57%).